2009
DOI: 10.1074/jbc.m109.020586
|View full text |Cite
|
Sign up to set email alerts
|

Procaspase 8 and Bax Are Up-regulated by Distinct Pathways in Streptococcal Pyrogenic Exotoxin B-induced Apoptosis

Abstract: We have previously identified integrin ␣ v ␤ 3 and Fas as receptors for the streptococcal pyrogenic exotoxin B (SPE B), and G308S, a mutant of SPE B that binds to Fas only. In the current study we found that after binding to ␣ v ␤ 3 , SPE B stimulated the tyrosine phosphorylation of JAK2 and STAT1. STAT1 tyrosine phosphorylation was inhibited by a JAK2 inhibitor, AG490, short interfering RNA (siRNA) silencing of JAK2, and anti-␣ V ␤ 3 antibody. AG490 also decreased the binding of tyrosine-phosphorylated STAT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…4C), its consequence on the p38 MAPK function was next examined in BV-2 and mouse primary microglial cells. We pretreated BV-2 and mouse primary microglial cells with the specific p38 MAPK inhibitor SB 203580 (Chang et al, 2009) and then treated the cells in the presence or absence of morphine. Apoptotic cells were examined by TUNEL assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C), its consequence on the p38 MAPK function was next examined in BV-2 and mouse primary microglial cells. We pretreated BV-2 and mouse primary microglial cells with the specific p38 MAPK inhibitor SB 203580 (Chang et al, 2009) and then treated the cells in the presence or absence of morphine. Apoptotic cells were examined by TUNEL assay.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of p38 MAPK by p38 inhibitor SB203580 significantly attenuated tolerance to morphine analgesia (Cui et al, 2006). P38 MAPK seems to sensitize cells to apoptosis by up-regulating Bax (Porras et al, 2004; Chang et al, 2009), a pro-apoptotic member of Bcl-2 family (Porras et al, 2004; Chang et al, 2009). But the role of p38 in morphine-promoted microglia apoptosis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Bcl2 is the first gene proven to be a negative regulator of cell death and to protect cells from undergoing apoptosis induced by exogenous stimuli, whereas Bax is a proapoptotic regulator that promotes or accelerates cell death (33). Our results provide evidence that the activation of the intrinsic apoptotic pathway via a Bcl-2 and Bax-dependent mechanism could be a possible mechanism by which TBMS1 enhances CDDP-induced apoptosis (Fig.…”
mentioning
confidence: 50%
“…8 Evidence also suggests that activated STAT1 may regulate apoptosis by enhancing the transcription of procaspase-8, Bax, Bcl-2, and Bcl-X. 10 STAT1 phosphorylated at serine 727 and tyrosine 701 can induce apoptotic cell death in heart, brain, and liver tissues following ischemia–reperfusion injury. In addition, it has been demonstrated that both serine 727 and tyrosine 701 of STAT1 are phosphorylated in response to JAK and p38 activation in Streptococcal pyrogenic exotoxin B-induced apoptosis.…”
mentioning
confidence: 99%
“…In addition, it has been demonstrated that both serine 727 and tyrosine 701 of STAT1 are phosphorylated in response to JAK and p38 activation in Streptococcal pyrogenic exotoxin B-induced apoptosis. 10 Although the proapoptotic effects of STAT1 have been widely reported, only a few studies have focused on its potential antiapoptotic properties. 11, 12 …”
mentioning
confidence: 99%